Automatic Vehicle Speed Contoller and Accident Detection System - Kumar, Bhuvanesh; Kumar, Dinesh; B. , Niteesh; R. , Manish; V.D. , Ambeth Kumar; A. , Mohan Vamsi (International Journal of Psychosocial Rehabilitation, 2020)
Speed control is the need of the hour due to the increased rate of accidents reported in our day-to-day lives. Nowadays, in this fast-moving world, people are not having self-control and are driving vehicles at excessive speeds and not following traffic rules properly in restricted areas. This is the main reason accidents and traffic jams are happening, and many people are being affected by being late to school or college, by emergency situations, and even by losing their precious lives. During an accident, the injured people have to face a lot of problems, such as the accident information received by the police being late or there being no one to help the injured people. So as to control the accidents and the traffic jams in restricted areas, we are using a sensor controlling unit and an automatic accident detection system, which are used in vehicles for emergency purposes. By using this concept, we can deduce the accident and traffic jams by following the traffic rules properly in restricted areas and even locate the vehicle that has made the accident.